Lung Manifestation of Collagen Vascular Disease in HRCT - Jagruti Kalola; Trivedi, Anjana; Happani, Hiral; Chauhan, Mohit (Asian Journal of Medical Radiological Research, 2020)
Background: The aim of this paper was to evaluate the thoracic manifestations associated with the Connective tissue disorders, with an emphasis on interstitial and airway disease pattern on the High Resolution computed tomography (HRCT) findings. Subjects and Methods: The present study was conducted for a period of one year. A total of 50 patients with various connective tissue disorders having respiratory complaints were evaluated. Results: During the study period 50 patients (80%females and 20%males) underwent evaluation. Cough and dyspnea were the most common presenting symptoms. Variety of thoracic abnormalities weredetected in 67 (95%) cases. Most common abnormality detected on HRCT was interstitial fibrosis/interstitial lung disease present in (60%) cases. Most common parenchymal abnormalities seen were reticulations (61.4%), ground glass opacification (40%), mosaic attenuation (32.8%) and honeycombing (24.3%). Airway abnormalities seen were bronchiectasis (48.5%), emphysema (12.8%), and ground glass nodules (2.8%). Conclusion: Interstitial lung disease is the most common pulmonary manifestation among patients with connective tissue disorders, and early detection and prompt treatment is expected to improve the outcome.